The design and assessment of an integrated municipal waste beneficiation facility : towards improved sewage sludge management in developing countries - Keirungi, Juliana (Rhodes University, Faculty of Science, Department of Environmental Science, 2007)
This research aimed to firstly confirm the hypothesis that the current management of sewage sludge generated during the treatment of wastewater in the Eastern Cape Province of South Africa is poor and, as such, this material poses a threat to local environmental and human health. Secondly, through a rational design approach, the current research also aimed to design and assess the suitability of a novel integrated process incorporating appropriate technologies for improved sewage sludge management. The lack of an appropriate tool for the assessment of the integrated process necessitated the development of an appropriate technology assessment (TA) methodology based on environmental, technical, social and economic criteria. A combination of informal participatory methods such as semi-structured interviews and formal research methods including questionnaires, risk assessment exercises and laboratory analyses were used. Based on the above it was estimated that 116 tons dry sludge were generated in the province per day and that the concentration of heavy metals present in the sludge was generally within the limits for reuse on agricultural land. Furthermore the sludge from all sample sewage treatment works (STWs) was found to be free of any detectable pathogens. Despite the above, a preliminary risk assessment and chemical analysis revealed that existing sludge management practices at sample STWs posed a threat to the environment, particularly to water resources and exacerbated the problems associated with the discharge of poorly treated municipal wastewater. The root causes of the poor sludge management were considered to be a lack of non-regulatory incentives and financial resources. Highly integrated ecologically engineered systems were thought to offer a solution to the dual problem of poor sludge management and municipal effluent treatment, while providing necessary economic incentives. To facilitate the design of a system appropriate to local conditions, it was necessary to first develop a rational design methodology, which incorporated a detailed TA step. The result of the design process was an Integrated Waste Beneficiation Facility (IWBF) that incorporated a number of process units comprised of appropriate technologies including composting, vermicomposting, algal ponding technology and aquaculture. A detailed TA indicated that the benefits of the proposed IWBF would, at the majority of sample sites, outweigh the potential negative impacts and it was thus recommended that investigations should continue on pilot-scale facilities. Furthermore, although the proposed TA based on four sustainability criteria categories was thought to provide a more accurate assessment of the true sustainability of a technology, the acquisition of information was problematic highlighting the need to re-think current TA methodologies and to address associated constraints allowing the tool to be used and fully comprehensive.
Keywords: Sewage -- Purification -- South Africa -- Eastern Cape; Sewage sludge -- South Africa -- Eastern Cape -- Management; Water quality management -- South Africa -- Eastern Cape